Gambaran Efektivitas Penerapan Program Rehabilitasi Stroke Berbasis Rumah di Kota Makassar - Yudi Hardianto; Rijal Rijal; Fadhia Adliah (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
This study aims to see a picture of the effectiveness of implementing a home-based stroke rehabilitation program. This research is a preliminary study involving 10 research subjects divided into 2 groups. Group 1 was given a rehabilitation program in the form of a physiotherapist's visit to provide exercise once a week. Group 2 was given 3 visits a week. A home-based stroke rehabilitation program in both groups was carried out for 1 month. In both groups, measurements of muscle strength, risk of falling and independence were measured. Each of the three variables was measured using a dynamometer, timed-up and go test, and functional independence measure (FIM). The results showed that group 2 had better muscle strength, risk of falls, and independence than group 1. This showed that in implementing a home-based stroke rehabilitation program, visits were more routine, at least 3 times a week, more recommended than visits that were only 1 time a week.